Clinical implications of the molecular biology of prostate cancer: Review article: Implicancias clínicas de la biología molecular del cáncer de próstata: Artículo de revisión - Castro-Mujica, María del Carmen (2022)
To understand the term genomic heterogeneity in prostate cancer, we must understand the clonal genomic evolution of cancer, as well as knowing that it is a dynamic and evolutionary phenomenon. Knowing the genome of prostate cancer not only allows us to have a vision over time of the genomic alterations that occur during its different stages, but also to learn about the mechanisms of metastasis. In addition, knowing the hereditary component of prostate cancer allows the evaluation of patients and to be able to identify if we are dealing with a family at risk.